Alpha lipoic acid supplementation attenuates reactive oxygen species in hypothalamic paraventricular nucleus and sympathoexcitation in high salt-induced hypertension. (22nd January 2016) - Su, Qing; Liu, Jin-Jun; Cui, Wei; Shi, Xiao-Lian; Guo, Jing; Li, Hong-Bao; Huo, Chan-Juan; Miao, Yu-Wang; Zhang, Meng; Yang, Qing; Kang, Yu-Ming
Highlights: The effect of chronic ALA supplementation on salt-induced hypertension is reported. High-salt diet induced increased proinflammatory cytokines and superoxide in PVN. High-salt diet induced oxidative stress in PVN, sympathoexcitation and hypertension. Chronic ALA supplementation attenuates ROS in PVN and sympathoexcitation. Chronic inhibiting superoxide attenuates RAS and cytokines in PVN in hypertension. Abstract: Aims: High salt-induced oxidative stress plays an important role in the development of hypertension. Alpha lipoic acid (ALA) is extensively recognized as having a powerful superoxide inhibitory property. In this study, we determined whether ALA supplementation attenuates oxidative stress in hypothalamic paraventricular nucleus (PVN), decreases the sympathetic activity and arterial pressure in high salt-induced hypertension by cross-talking with renin–angiotensin system (RAS) and pro-inflammatory cytokines (PICs). Methods: Male Wistar rats were administered a normal-salt diet (NS, 0.3% NaCl) or a high-salt diet (HS, 8.0% NaCl) for 8 weeks. These rats received ALA (60 mg/kg) dissolved in vehicle (0.9% saline) or an equal voleme of vehicle, by gastric perfusion for 9 weeks. Results: High salt intake resulted in higher renal sympathetic nerve activity (RSNA) and mean arterial pressure (MAP). These rats also had higher levels of superoxide, gp91 phox, gp47 phox (subunits of NAD(P)H oxidase), angiotensin-converting enzyme (ACE), angiotensin II type1 receptor (AT1-R), interleukin-1beta (IL-1β), interleukin-6 (IL-6), and lower levels of interleukin-10 (IL-10) and copper/zinc superoxide dismutase (Cu/Zn-SOD) than control animals. Treatment with ALA significantly attenuated the levels of superoxide, gp91 phox, gp47 phox, ACE, AT1-R, IL-1β and IL-6, increased the levels of IL-10 and Cu/Zn-SOD, and decreased MAP and RSNA compared with high-salt induced hypertensive rats. The mRNA expression of gp47 phox and gp91 phox are in accordance with their protein expression. Conclusion: These findings suggest that supplementation of ALA obviously decreases the sympathetic activity and arterial pressure in high salt-induced hypertension by improving the superoxide inhibitory property, suppressing the activation of RAS and restoring the balance between pro- and anti-inflammatory cytokines in the PVN.